2007
DOI: 10.1371/journal.pone.0001320
|View full text |Cite
|
Sign up to set email alerts
|

Alloxan-Induced Diabetes Triggers the Development of Periodontal Disease in Rats

Abstract: BackgroundPeriodontal disease in diabetic patients presents higher severity and prevalence; and increased severity of ligature-induced periodontal disease has been verified in diabetic rats. However, in absence of aggressive stimuli such as ligatures, the influence of diabetes on rat periodontal tissues is incompletely explored. The aim of this study was to evaluate the establishment and progression of periodontal diseases in rats only with diabetes induction.Methodology/Principal FindingsDiabetes was induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
39
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 41 publications
4
39
0
4
Order By: Relevance
“…41,42,43 Elevated serum LDH activity is a reliable clinical indicator of organ injuries, especially those adversely affected by DM pathology and chemical toxicity, namely, the heart, liver and muscle. 9,10,11 The relatively raised level of serum LDH activity was obvious indication of systemic toxicity occasioned by tissue necrosis as exemplified in alloxan-induced DM rat (Group 2; DIAB). In clinical diagnosis, LDH activity is relatively low in serum in absence of cellular injuries, whereas raised level of serum LDH activity is a reflection of tissue infarction and/ or necrosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…41,42,43 Elevated serum LDH activity is a reliable clinical indicator of organ injuries, especially those adversely affected by DM pathology and chemical toxicity, namely, the heart, liver and muscle. 9,10,11 The relatively raised level of serum LDH activity was obvious indication of systemic toxicity occasioned by tissue necrosis as exemplified in alloxan-induced DM rat (Group 2; DIAB). In clinical diagnosis, LDH activity is relatively low in serum in absence of cellular injuries, whereas raised level of serum LDH activity is a reflection of tissue infarction and/ or necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical diagnosis, LDH activity is relatively low in serum in absence of cellular injuries, whereas raised level of serum LDH activity is a reflection of tissue infarction and/ or necrosis. 9,10,11 and parallels the number of necrotic cells. 46 Previous reports have shown that RONS mediated tissue necrosis, as a result of alloxan/streptozotocin intoxication in concert with the pathophysiology of DM, contributed to organ injuries and was a reflection of raised levels of serum LDH activity in DM rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Claudino et al [2007], alveolar bone loss was radiographically detectable in alloxan-induced diabetic rats only 3 months after the onset of DM1. In this study, the animals had had confirmed DM1 for at least 2 weeks before the beginning of the experiments (time zero), so that maximum exposure to DM1 was 45 days.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, alloxan-induced diabetes in rats triggers, or co-induces, the onset of alterations that are typical of periodontal diseases even in the absence of aggressive factors such as ligatures or inoculation of classic periodontopathogens. 53 In this context, it is important to consider that experimental arthritis development does not alter the pattern of periodontal infection (the A. actinomycetemcomitans and overall bacterial loaddata not shown), ruling out the possible increased responsiveness because of an increased microbial challenge. Indeed, as earlier discussed, clinical studies show that RA/PD interaction is only partially dependent on oral hygiene status and the control of oral flora.…”
Section: Experimental Periodontitis and Arthritis Interaction Ap Trommentioning
confidence: 99%